2022
DOI: 10.7498/aps.71.20220774
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of photonic reservoir computing using short internal cavity laser

Abstract: With the advent of the high-speed information age and the explosive of information, higher requirements are placed on the information processing speed. In recent years, researchers have carried out a lot of research on delay-based reservoir computing (RC) systems. Meanwhile, the improvement of information processing rate mainly revolves around the replacement of nonlinear nodes in the system. However, as the most frequently used distributed feedback semiconductor (DFB) laser, many researchers only use ordinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…In Formula ( 6): q n i,j is the flow rate from well j to well i; m 3 /s. Considering the influence of edge and bottom water in the reservoir, it is deduced according to the theory of front edge propulsion [26][27][28]. By setting an upstream node position x u of x, the saturation of the corresponding node position is S wu , and it is concluded that:…”
Section: Model Moisture Content Solutionmentioning
confidence: 99%
“…In Formula ( 6): q n i,j is the flow rate from well j to well i; m 3 /s. Considering the influence of edge and bottom water in the reservoir, it is deduced according to the theory of front edge propulsion [26][27][28]. By setting an upstream node position x u of x, the saturation of the corresponding node position is S wu , and it is concluded that:…”
Section: Model Moisture Content Solutionmentioning
confidence: 99%